Effect of implant strategy and Optaflexx administration on feedlot performance and skeletal muscle β-adrenergic receptor and insulin-like growth factor I mRNA abundance - Sisson, E.K.; Hutcheson, J.P.; Yates, D.A.; Johnson, B.J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Feedlot heifers (1,147) weighing 622 lb were used to evaluate the effects of implant strategy and Optaflexx administration. Implant treatments included Revalor-200 (R200) at arrival, or Revalor-IH at arrival and reimplantation with Finaplix-H on day 58 (RF). Optaflexx (200 mg/heifer daily of ractopamine-HCl) was fed the last 28 days. Treatments were randomly assigned to 16 pens. After 182 days, heifers were slaughtered, at which time carcass data were obtained and semimembranosus muscle tissue was excised for RNA isolation. Optaflexx administration significantly increased average daily gain (0.7 lb/day), feed efficiency (3%), hot carcass weight (10.5 lb), and ribeye area (0.42 square inches); decreased back fat thickness; and improved yield grade. There was no significant treatment effect on the expression of β1-adrenergic receptor (AR) mRNA, but there was a tendency for Optaflexx feeding to increase β2-AR mRNA concentrations. For β3-AR mRNA, Optaflexx treatment numerically increased β3-AR mRNA in heifers implanted with R200, but significantly decreased expression in heifers implanted with RF. Optaflexx also significantly decreased IGF-I mRNA in heifers implanted with RF, but numerically increased IGF-I mRNA in heifers implanted with R200. This data aids our understanding of the interaction between steroidal implants and Optaflexx in feedlot heifers. Knowledge about the modes of action of various growth promotants will aid in designing growth promotion strategies to enhance the efficiency of lean tissue deposition in feedlot cattle.
Keywords: Beef; Optaflexx; Performance; Skeletal muscle; β-adrenergic receptor; mRNA